Hypertension Control in the United States 2009 to 2018: Factors Underlying Falling Control Rates During 2015 to 2018 Across Age- and Race-Ethnicity Groups. Issue 3 (14th June 2021) - Egan, Brent M.; Li, Jiexiang; Sutherland, Susan E.; Rakotz, Michael K.; Wozniak, Gregory D.
Abstract : Supplemental Digital Content is available in the text. Abstract : Hypertension control (United States) increased from 1999 to 2000 to 2009 to 2010, plateaued during 2009 to 2014, then fell during 2015 to 2018. We sought explanatory factors for declining hypertension control and assessed whether specific age (18–39, 40–59, ≥60 years) or race-ethnicity groups (Non-Hispanic White, NH [B]lack, Hispanic) were disproportionately impacted. Adults with hypertension in National Health and Nutrition Examination Surveys during the plateau (2009–2014) and decline (2015–2018) in hypertension control were studied. Definitions: hypertension, blood pressure (mm Hg) ≥140 and/or ≥90 mm Hg or self-reported antihypertensive medications (Treated); Aware, 'Yes" to, "Have you been told you have hypertension?"; Treatment effectiveness, proportion of treated adults controlled; control, blood pressure <140/<90. Comparing 2009 to 2014 to 2015 to 2018, blood pressure control fell among all adults (−7.5% absolute, P <0.001). Hypertension awareness (−3.4%, P =0.01), treatment (−4.6%, P =0.004), and treatment effectiveness (−6.0%, P <0.0001) fell, despite unchanged access to care (health care insurance, source, and visits [−0.2%, P =0.97]). Antihypertensive monotherapy rose (+4.2%, P =0.04), although treatment resistance factors increased (obesity +4.0%, P =0.02, diabetes +2.3%, P =0.02). Hypertension control fell across age (18–39 [−4.9%, P =0.30]; 40–59 [−9.9%, P =0.0003]; ≥60 years [−6.5%, P =0.005]) and race-ethnicity groups (Non-Hispanic White [−8.5%, P =0.0007]; NHB −7.4%, P =0.002]; Hispanic [−5.2%, P =0.06]). Racial/ethnic disparities in hypertension control versus Non-Hispanic White were attenuated after adjusting for modifiable factors including education, obesity and access to care; NHB (odds ratio, 0.79 unadjusted versus 0.84 adjusted); Hispanic (odds ratio 0.74 unadjusted versus 0.98 adjusted). Improving hypertension control and reducing disparities require greater and more equitable access to high quality health care and healthier lifestyles.